An Impact of Distance Learning for Elementary School Students in SDN 11 Teluk Betung Pesisir Selatan - Juita, Erna; Dasrizal, Dasrizal; Suryadi, Suryadi; Nita, Rahma Wira; Sandra, Heru Kartika (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aims to determine how the impact of distance learning experienced by teachers and students during the COVID-19 pandemic. This study uses qualitative research methods, where in collecting information data with interview techniques, in order to find data on relevant matters. The subjects of this study were students of SDN 11 Teluk Betung Pesisir Selatan. The results showed that the distance learning process did not run optimally and there were several obstacles for teachers and students in distance learning.